2017
DOI: 10.7754/clin.lab.2017.170522
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-150 as a Potential Biomarker in Diagnosis of Cancer: a Meta-Analysis

Abstract: miR-150 may be a potential noninvasive tumor marker for various human cancers and further studies with a large sample size are needed to confirm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…PubMed, Embase, and Web of Science for publications were searched using the keywords of miR-150 and human cancer. (J. Yan et al 2017 , p. 1187)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PubMed, Embase, and Web of Science for publications were searched using the keywords of miR-150 and human cancer. (J. Yan et al 2017 , p. 1187)…”
Section: Resultsmentioning
confidence: 99%
“…(Wang et al 2017 , p. 59666) PubMed, Embase, and Web of Science for publications were searched using the keywords of miR-150 and human cancer. (J. Yan et al 2017 , p. 1187) We searched in EBSCO, PsycINFO, Google Scholar, Web of Science , and NCBI databases and other articles manually from lists of references of extracted articles. (Piqueras, Martín-Vivar, Sandin, San Luis, & Pineda 2017 , p. 153) The same pattern was found for the four other top verbs listed in Table 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Receiver operating characteristic curve (ROC) analysis confirmed that plasma miR-145 is a candidate biomarker for detecting cervical cancer and differentiating complete responders from incomplete responders ( Wei et al, 2017 ). Yan et al (2017) carried out a meta-analysis that included 7 original studies (data from PubMed, Embase, and Web of Science), and discovered that miR-150 may be a potential non-invasive tumor marker for various human cancers (leukemia, colorectal, hepatocellular, and lung cancer) ( Yan et al, 2017 ). Besides, a total of 73 patients with papillary thyroid carcinoma were enrolled.…”
Section: Theranostic Value Of Mir In Rectal Cancermentioning
confidence: 99%
“…The abnormal expression of miRNA is associated with a variety of diseases including tumors (7). miRNA has been demonstrated to be involved in the regulation of tumor cell proliferation, apoptosis, differentiation, drug resistance, invasion and metastasis, among which miR-150 also ion, drug resistance, invasion and metastasis, among which miR-150 also serves an important role in the development of tumors (10)(11)(12)(13)(14)(15). In colorectal cancer, breast cancer and melanoma, miR-150 is significantly downregulated and exerts a tumor suppressive role (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…However, in cervical cancer, miR-150 is highly expressed and promotes tumor progression (14). Therefore, miR-150 serves different roles in different tumor types (10)(11)(12)(13)(14). miR-150-5p, a member of the miR-150 family, has been determined to inhibit cancer cell aggressiveness by targeting cwcv and kazal like domains proteoglycan 1 in head and neck squamous cell carcinoma (15).…”
Section: Introductionmentioning
confidence: 99%